PENERAPAN MODEL PEMBELAJARAN KOOPERATIF INSIDE OUTSIDE CIRCLE (IOC) UNTUK MENINGKATKAN HASIL BELAJAR IPA FISIKA DI SMP NEGERI 1 LUBUK DALAM KABUPATEN SIAK - Fivi Efendi; Zuhdi Ma’aruf; Muhammad Nasir (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2018)
Abstract: The aim of this research is to describe the improvement of cognitive learning outcomes of Physics IPA through the implementation of cooperative learning Inside Outside Circle (IOC). This research was conducted at SMP Negeri 1 Lubuk Dalam from April to Mei 2018. Sample choice from homogeneous classes. Quasi experiments in the form of intact group comparison was used in this study. The sample of the study were the students of class VII5 as the experimental class and class VII4 as the control class. The data was obatained from cognitive learning result test which consisted of 15 items of multiple choice. Data analysis techniques used descriptive and inferential analysis. The results showed that the average ability of students with the application of cooperative learning model Inside Outside Circle (IOC) is higher conventional learning.It can be concluded that the application of cooperative learning model Inside Outside Circle (IOC) can improve learning outcomes ofPhysics IPA in SMP Negeri 1Lubuk Dalam Siak Regencyon indication of Solar System.Keywords: Cooperative Learning,Inside Outside Circle, Cognitive Learning Outcomes